An integrated core-based analysis for the characterization of flow, transport and mineralogical parameters of the Heletz pilot CO2 storage site reservoir. (May 2016) - Bogdan Tatomir, Alexandru; Halisch, Matthias; Duschl, Florian; Peche, Aaron; Wiegand, Bettina; Schaffer, Mario; Licha, Tobias; Niemi, Auli; Bensabat, Jacob; Sauter, Martin
Highlights: A suite of laboratory and pore-scale CT-based modeling techniques are employed to determine the flow and transport parameters of Heletz sandstone (pore and grain size distribution, porosity, permeability, surface are of the pore space, tortuosity and capillary pressure–saturation relationships). The amounts of minerals and the poor binding of the Heletz sandstone are revealed through cathodoluminescence microscopy, SEM/XRD and digital image analysis (DIA) on thin sections. Porosity is determined from μ-CT reconstructed geometries and experimentally from buoyancy method, mercury intrusion porosimetry (MIP), and DIA. Permeability is determined from gas permeametry at ambient and overburden pressures, and μ-CT based Stokes modeling. Permeability, capillary pressure–saturation relationships and surface area of the pore space from the μ-CT geometries are significantly affected by the scanning resolution. Abstract: Heletz, Israel is the location for an onshore deep saline CO2 storage pilot site. The ' Heletz sandstone ' is the building unit of the deep saline reservoir. Based on core samples of sandstone and caprock taken from the newly drilled injection (H18A) and monitoring wells (H18B), this article examines and reports the petrophysical properties of the Heletz Formation reservoir important for the short and long term trapping of CO2 . A suite of laboratory and pore-scale CT-based modeling techniques are employed to determine the flow and transport parameters used by the continuum-scale numerical simulators and the mineral composition necessary for the understanding of mineral trapping processes. The effect of diagenesis on the reservoir parameters was determined in the laboratory using sedimentological, petrological, and petrophysical analyses. Variations in 87 Sr/ 86 Sr isotope composition and fluid inclusion analysis bring additional information about the diagenetic development and define the status quo of fluid–mineral reactions before CO2 injection. Cathodoluminescence microscopy and SEM/XRD revealed the amounts of minerals in the sandstone samples and caprock and explained the poor binding of the sandstone which may lead to mobilized material during injection. Digital image analysis on thin sections, cathodoluminescence, and SEM were integrated with attributes derived from mercury intrusion porosimetry, steady state gas permeametry or nuclear magnetic resonance to form an essential outline for the Heletz Formation reservoir. This relates storage space, injectivity and storage efficiency to features such as grain size, pore size distribution, effective porosity, intrinsic permeability, or tortuosity. Furthermore, the laboratory and numerical CT-based investigation techniques are compared and discussed. The benefit of combining experimental methods and numerical simulations on pore-scale models is the increase in confidence of the parameter accuracy, fundamental for the success of the planned activities at Heletz.